Oxygen carriers from incineration bottom ash for chemical looping combustion of syngas: effect of composition on combustion efficiency - Yin, Ke (2022)
Incineration bottom ashes (IBA) were investigated as oxygen carriers (OCs) for their application in chemical looping combustion (CLC). The OCs were prepared by mixing the magnetic separated fraction of IBA (IMF) with its non-magnetic fraction (NMF) at various ratios. Additionally, a synthesized iron oxide supported on the pre-washed IBA (0, 25, 50 and 75 wt%), termed as synFe, were also investigated for comparison with the investigated IMF. Thermogravimetric analysis (TGA) combined with elemental analysis unveiled that Fe2O3 and CaSO4 in IMFs were the major sources of the available lattice oxygen in the investigated oxygen carriers. A synergistic effect was observed among the complex components in IMF-based OCs causing the experimental oxygen transport capacity to be larger than the theoretically expected, calculated based on the metal oxides (including Fe2O3, CuO, Mn2O3 and NiO) and CaSO4 redox couples. A syngas (H2 + CO) combustion tests with the IMF-based OCs in a bench-scale fluidized bed reactor were conducted, where the100-IMF demonstrated the most pronounced and stable combustion performance (95% for H2 and 90% for CO), comparable to those delivered by 50% and 75% synFe. Based on this study, the IMF compounds from the raw IBA without any further treatment carry a high potential for CLC process, which provides possible option of a cost-effective OCs and sustainable application of IBA.